Recycling of plastic materials - La Mantia, Francesco Paolo (ChemTec Pub., 1993)
Combines topics discussing the state of art, analysis of processes successfully implemented in industrial practice, ideas concerning production with recycling in mind, and the new research developments offering practical solutions for recycling industry and product manufacturers. The major emphasis is given to polyolefins, polyethylene terephthalate, PVC, and rubber. Materials concerned include films, bottles, packing materials, paper, car batteries, plastics used in car interiors, tires, etc.
Keywords: Plastics -- Recycling.; elektronické knihy; electronic books